A laboratory perspective on Mycobacterium abscessus biofilm culture, characterization and drug activity testing - Meliefste, Henriëtte Margarethe; Mudde, Saskia Emily; Ammerman, Nicole Christine; de Steenwinkel, Jurriaan Evert M.; Bax, Hannelore Iris (Frontiers in Microbiology, 2024)
Mycobacterium abscessus is an emerging opportunistic pathogen causing severe pulmonary infections in patients with underlying lung disease and cystic fibrosis in particular. The rising prevalence of M. abscessus infections poses an alarming threat, as the success rates of available treatment options are limited. Central to this challenge is the absence of preclinical in vitro models that accurately mimic in vivo conditions and that can reliably predict treatment outcomes in patients. M. abscessus is notorious for its association with biofilm formation within the lung. Bacteria in biofilms are more recalcitrant to antibiotic treatment compared to planktonic bacteria, which likely contributes to the lack of correlation between preclinical drug activity testing (typically performed on planktonic bacteria) and treatment outcome. In recent years, there has been a growing interest in M. abscessus biofilm research. However, the absence of standardized methods for biofilm culture, biofilm characterization and drug activity testing has led to a wide spectrum of, sometimes inconsistent, findings across various studies. Factors such as strain selection, culture medium, and incubation time hugely impact biofilm development, phenotypical characteristics and antibiotic susceptibility. Additionally, a broad range of techniques are used to study M. abscessus biofilms, including quantification of colony-forming units, crystal violet staining and fluorescence microscopy. Yet, limitations of these techniques and the selected readouts for analysis affect study outcomes. Currently, research on the activity of conventional antibiotics, such as clarithromycin and amikacin, against M. abscessus biofilms yield ambiguous results, underscoring the substantial impact of experimental conditions on drug activity assessment. Beyond traditional drug activity testing, the exploration of novel anti-biofilm compounds and the improvement of in vitro biofilm models are ongoing. In this review, we outline the laboratory models, experimental variables and techniques that are used to study M. abscessus biofilms. We elaborate on the current insights of M. abscessus biofilm characteristics and describe the present understanding of the activity of traditional antibiotics, as well as potential novel compounds, against M. abscessus biofilms. Ultimately, this work contributes to the advancement of fundamental knowledge and practical applications of accurate preclinical M. abscessus models, thereby facilitating progress towards improved therapies for M. abscessus infections.